Tahap Persediaan dan Kerugian Para Peniaga Ketika Banjir Ekstrem 2014: Kajian Kes Bandar Kuala Krai, Kelantan: Preparedness and Losses Level of Traders during Extreme Flood 2014: A case study of Bandar Kuala Krai, Kelantan - See, Koh Liew; Nayan, Nasir; Mahat, Hanifah; Hashim, Mohmadisa; Saleh, Yazid; A. Rahaman, Zullyadini; Taleha, Nur Anizah (GEOGRAFI, 2017)
Flood preparedness among the traders played an important role in minimizing the damage caused by flood. This is because thorough preparedness will help traders to be vigilant and cautious when receiving a warning about the impending floods. This study aims is to examine the relationship between preparedness level and the level of losses experienced by traders during the flood in 2014. Questionnaires were used in this study to collect primary data. A total of 175 respondents were selected using random sampling method. The analysis used was crosstab and descriptive analysis. The study found that the traders who have high preparedness level will experienced low losses during the flood in 2014. Thus, flood preparedness is the best approach to be practiced by the traders in Bandar Kuala Krai to reduce damage and losses due to flooding.